An Evolving University-School Partnership: The University of Notre Dame Magnificat Schools - Dallavis, Christian; Johnstone, Joyce (Catholic Education: A Journal of Inquiry and Practice, 2009)
For the past 15 years, Catholic colleges and universities have developed programs serving Catholic K-12 schools by preparing teachers and leaders for Catholic school contexts. University-school partnerships provide an opportunity for Catholic institutions of higher education to extend beyond developing human resources to strengthen Catholic K-12 schools to effect comprehensive school reform. This article describes the origins and evolution of one such university-school partnership initiative, the University of Notre Dame’s Magnificat School partnerships. This article presents an analysis of program evaluation data from the first 3 years of the Magnificat partnerships and a discussion of how the lessons learned in this program evaluation have informed revisions to the Magnificat model. Additionally, these lessons can inform the efforts of other colleges and universities that may seek to engage Catholic K-12 schools to effect comprehensive school reform.